Identifying missed clinical opportunities for the earlier diagnosis of HIV in Australia, a retrospective cohort data linkage study - Mallitt, Kylie-Ann (PLoS One, 2018)
BACKGROUND: Treatment as prevention approaches for HIV require optimal HIV testing strategies to reduce undiagnosed HIV infections. In most settings, HIV testing strategies still result in unacceptably high rates of missed and late diagnoses. This study aimed to identify clinical opportunities for targeted HIV testing in persons at risk to facilitate earlier HIV diagnosis in New South Wales, Australia; and to assess the duration between the diagnosis of specific conditions and HIV diagnosis. METHODS: The Australian National HIV registry was linked to cancer diagnoses, notifiable condition diagnoses, emergency department presentations and hospital admissions for all HIV diagnoses between 1993 and 2012 in NSW. Date of HIV acquisition was estimated from back-projection models and people with a likely duration from infection to diagnosis of less than 180 days were excluded. Risk factors associated with clinical opportunities for the earlier diagnosis of HIV were identified. RESULTS: Sexually transmitted infection diagnoses (particularly gonorrhoea and syphilis) and some hospital admissions (mental health and drug-related diagnoses, and non-infective digestive disorder diagnoses) were prominent among people estimated to be living with undiagnosed HIV. The length of time between a clinical opportunity for the earlier HIV diagnosis and actual HIV diagnosis was 13.3 months for notifiable conditions, and 15.2 months for hospital admissions. People with lower CD4+ cell count at diagnosis, and older people were significantly less likely to have a missed opportunity for earlier HIV diagnosis. CONCLUSIONS: Additional targeted clinical HIV testing strategies are warranted for people with gonorrhoea and syphilis; and hospital presentations or admissions for mental health, drug-related and gastrointestinal diagnoses.